METHOD FOR MEASURING MOTION PARAMETERS OF MOVING OBJECTS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The paper considers a new method for measuring the angular deviations of moving objects. A specific measuring system is proposed to measure ship roll, pitch, heel and trim. The system consists of two measurement channels operating in parallel. The first channel is built on the position properties of a physical pendulum so as to build the base vertical. The second channel ensures the dynamic accuracy of the system. The principal of operation of the second channel involves correction of the signals from the first channel by using information obtained from linear MEMS accelerometers. To increase system measurement accuracy, a signal processing module is used through the Kalman filter algorithm.